الوسطية في الإسلام كما فهمها وبيّنها الإمام الصيني الشهيد يوسف تشن كه لي في كتابه 《معرفة الإسلام عن طريق معرفة محمد 》 = Moderation in Islam as understood and demonstrated by the imam Martyr Yusuf Chen Ke Li in his book (Knowing Islam by knowing Mohamed (s.a.w)) - Ma Zhengbin, Yunus Abdullah (Al- Azhar University, 2021)
The research entitled above consists of an introduction, three sections, and a conclusion. The introduction discusses the academic personality of the Chinese imam, the Martyr Yusuf Chen Keli. The first section presents imam’s idea on the relevance of Islam across different cultures and generations. The second section revolves around providing practical samples for moderation in Islam. The third section presents a comprehensive and fair view of Islam towards the dunya and akhirah.